ChemInform Abstract: Direct Measurements of Particle—Surface Interactions in Aqueous Solutions with Total Internal Reflection Microscopy. Issue 30 (29th July 2014) - Gong, Xiangjun; Wang, Zhaohui; Ngai, To
Abstract Review: 89 refs.